Komunikasi Internal Dan Efektivitas Kerja Karyawan(Studi Korelasi Komunikasi Internal Terhadap EfektivitasKerja Karyawan dalam Melaksanakan Fungsi Organisasi Pada Perusahaan Daerah Taman Satwa Taru Jurug Surakarta Tahun 2014) - Kencana, Randy Puspita, Dian Purworini, S.Sos., M.M, Nieldya Nofrandilla, MA (2015)
The aim of this research is to examine correlation between internal communications and employee's work effectiveness of PERUSDA TSTJ Surakarta. Quantitative research method is used for thesis arrangement. Researcher using data collecting technique with questionnaire, observation, and literature review that related to research. The research result showing that relationship between internal communications to employee's work effectivity is significant and low positivity. Shown with Product Moment Correlations formula, coefficient correlations has low relationship with the acquisition results 0,29 it seen by low score of employee's work effectivity variable. Research variable connections which suitable with observation results in organization such as early briefing, job offering, relational, control and production related with organizational internal's communication. Then, to show organizational work's effectivity by quality and quantity, employee's duty, timeliness in completing the task, and independence employees to provide the best outcome.